Practical formal synthesis of D-(+)-biotin from 4-formylazetidin-2-one - Kale, Ajaykumar S.; Puranik, Vedavati G.; Deshmukh, Abdul Rakeeb A. S. (Synthesis-Stuttgart, 2007)
A practical synthesis of (3S,6R)-1,3-dibenzyltetrahydro-1H-furo[3,4-d]imidazole-2,4-dione, an important intermediate in the synthesis of biotin, from 4-formyl-3-mesyloxyazetidin-2-one has been achieved. Acid-catalyzed azetidin-2-one ring opening followed by a one-pot conversion of diamine hydrochloride to a cyclic urea and hydroxymethylene to chloromethylene by triphosgene to obtain (4S,5R)-methyl-1,3-dibenzyl-5-chloromethyl-2-oxoimidazolidine-4-carboxyl ate is the key step in this synthesis.
Keywords: azetidin-2-one; beta-Lactams; cyclization; Lactone; reduction

Combined experimental and density functional theory study on the Pd-mediated cycloisomerization of o-alkynylnitrobenzenes - synthesis of isatogens and their evaluation as modulators of ROS-mediated cell death - Ramana, Chepuri V.; Patel, Pitambar; Vanka, Kumar; Miao, Benchun; Degterev, Alexei (European Journal of Organic Chemistry, 2010)
Highly selective cycloisomerization of o-alkynylnitrobenzenes, leading to isatogens, has been achieved by employment of a Pd-II complex. This reaction is very general and functional-group-tolerant. The possible mechanism of this reaction was investigated with the help of DFT calculations. Three possible pathways - namely, the addition of the nitro group either in (i) 5-exo-dig or (ii) 6-endo-dig mode and (iii) halopalladation - and subsequent intramolecular events have been considered and studied in detail. These investigations revealed that pathway (i) is the favored route to isatogen formation. A preliminary screening of the available isatogens reveals the 2-alkylisatogens to be novel ROS scavengers capable of inhibiting cellular necroptosis.
Keywords: Anthranil; cyclization; Density functional calculations; isatogens; Nitro-alkyne cycloisomerization; Palladium

Highly diastereoselective total synthesis of (+/-)-heritonin and (+/-)-heritol - Chavan, Subhash P.; Garai, Sumanta; Kalkote, Uttam R. (Tetrahedron, 2012)
A highly diastereoselective synthesis of heritol and heritonin by intramolecular cyclization on a preformed sensitive butenolide functionality is described. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Butenolide; cyclization; Dihydroxylation; Friedel-Crafts acylation; Tetralone

Concise synthesis of (5R,6S)-tert-butyl 5-acetoxy-6-(hydroxymethyl)-5,6-dihydropyridine-1(2H)-carboxylate - Ramalingam, S.; Bhise, Ankushkumar D.; Show, Krishanu; Kumar, Pradeep (Arkivoc, 2013)
An efficient synthesis of (5R,6S)-tert-butyl 5-acetoxy-6-(hydroxymethyl)-5,6-dihydropyridine-1(2H)-carboxylate 1, a common intermediate for various polyhydroxylated piperidines is reported in six steps with 32% overall yield starting from Garner's aldehyde. The key steps include the diastereoselective nucleophilic addition and intramolecular cyclization. (5R,6S)-tert-butyl 5-acetoxy-6-(hydroxymethyl)-5,6-dihydropyridine-1(2H)-carboxylate is a common precursor for the synthesis of 1-deoxy-L-mannojirimycin, 1-deoxy-L-idonojirimycin, L-fagomycin and related analogues.
Keywords: cyclization; Garner's aldehyde; nucleophilic addition; polyhydroxy piperidines

Target cum flexibility: simple access to benzofuran conjugated sugar and nucleoside derivatives - Kommagalla, Yadagiri; Srinivas, Kolluru; Ramana, C. V. (Tetrahedron Letters, 2013)
The [Pd]-catalyzed domino process comprising of the coupling of alkynes and o-iodophenol and the subsequent cyclization leading to benzofurans has been successfully applied on the sugar and nucleoside derived alkynes. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Benzofuran; carbohydrates; cyclization; Nucleoside; Palladium

Croncise organocatalytic route to protected (2S, 4R)-4-hydroxyornithine and(+)-pseudohygroline - Jha, Vishwajeet; Kumar, Pradeep (Synlett, 2014)
A practical, efficient, and organocatalytic approach to the synthesis of (2S,4R)-4-hydroxyornithine and (+)-pseudohygroline is reported using proline-catalyzed sequential alpha-aminoxylation/alpha-amination reaction and Horner-Wadsworth-Emmons olefination reaction of an aldehyde as the key step.
Keywords: aldehydes; Amination; Amino alcohols; cyclization; Enantioselectivity; Wittig reaction

One-pot synthesis of cyclic carbonates from aldehydes, sulfur ylide, and CO2 - Aher, Ravindra D.; Kumar, B. Senthil; Sudalai, Arumugam (Synlett, 2014)
Treatment of aldehydes with sulfur ylide (CH2=SOMe2 or CH2=SMe2), in the presence of CO2 (1 atm) bubbled sequentially under mild conditions, produces cyclic carbonates in preparative yields. Sodium iodide formed in situ promotes the reaction between epoxide as intermediate and CO2 at ambient conditions, thus constituting a powerful metal-free synthesis of organic cyclic carbonates directly from aldehydes.
Keywords: Carbon dioxide; cyclic carbonates; cyclization; epoxides; Insertion

Synthesis of (+)-harmicine - Mondal, Pravat; N. P. Argade (Synthesis-Stuttgart, 2014)
A facile convergent access to the important indole alkaloid (+)-harmicine is described, starting from tryptamine and (R)-acetoxysuccinic anhydride via the corresponding acetoxysuccinimide in very good overall yield. Regioselective reduction of an unsymmetrical imide carbonyl group and acid-catalyzed stereoselective intramolecular cyclization were the key features involved. The directing group to induce asymmetry was finally detached via the corresponding iodide by using tributyltin hydride chemistry.
Keywords: alkaloids; cyclization; imides; reduction; stereoselective synthesis

Formal syntheses of (2R,3R)-3-hydroxy pipecolic acid and (2R,3S)-3-hydroxy pipecolic acid from L-ascorbic acid - Chavan, Subhash P.; Dumare, Nilesh B.; Pawar, Kailash P. (Tetrahedron Letters, 2015)
Formal syntheses of both cis and trans 3-hydroxy pipecolic acids is achieved from L-ascorbic acid. Present synthesis describes use of chiral pool approach in which epimerization, Staudinger reaction and Cyclization reactions were employed as key steps. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: 3-Hydroxy pipecolic acid; cyclization; Epimerization; L-Ascorbic acid

Synthesis of 3-ethyl-4-metyl-1h,5-dihydro-2h-pyrrol-2-one by novel palladium(ii)-catalyzed cyclization and ring-closing metathesis - Chavan, Subhash P.; Pathak, Ashok B.; Pawar, Kailash P. (Synthesis-Stuttgart, 2015)
Synthesis of 3-ethyl-4-methyl-1,5-dihydro-2H-pyrrol-2-one is described starting from commercially available allylamine and 4-methoxybenzylamine employing palladium-catalyzed cyclization or ring-closing metathesis as the key steps.
Keywords: antidiabetic; cyclization; glimepiride; lactams; metabolite; pyrrolinone; Ring-closing metathesis

Apparent umpolung reactivity of indole through [Au]-catalysed cyclisation and lewis-acid-mediated allylation - Shinde, Mahesh H.; Ramana, Chepuri V. (Chemistry-A European Journal, 2020)
The sequential functionalization of indole C2 and C3 in an umpolung fashion was executed with a predesigned substrate and choice of reagents. The developed method comprises gold-catalysed alkynol cycloisomerisation/intramolecular addition of C2 of indole and subsequent BF3.OEt2-mediated regioselective C3 allylation, resulting in the synthesis of the functionalized indoloisoquinolinone scaffold. The reaction involves 5-endo-alkynol cycloisomerisation and the dearomative addition of indole C2 to the intermediate oxocarbenium cation, which results in two equilibrating fused and spiropentacyclic intermediates, which upon treatment with allyl silane in the presence of BF3.OEt2, undergo selective indole C3 allylation. Other nucleophiles, such as hydride, azide and indole, were also found to be compatible with this process.
Keywords: Allylation; cyclization; domino reactions; Gold; umpolung

cis-aziridine synthon based synthetic investigation for tamiflu employing horner-wadsworth-emmons reaction - Chavan, Subhash P.; Kawale, Sanket A.; Gonnade, Rajesh G. (European Journal of Organic Chemistry, 2022)
Synthetic investigations to achieve a novel intermediate of Tamiflu by using cis-aziridine as a chiral building block, which is readily synthesized from (D)-mannitol as a renewable starting material, has been presented. The present approach utilizes the intramolecular Horner-Wadsworth-Emmons reaction as the key step for the synthesis of Tamiflu. On the other hand, diene containing allylic aziridine framework is found to be inefficient to furnish the six-membered core skeleton of Tamiflu through ring-closing metathesis reaction.
Keywords: Aziridine; cyclization; HWE reaction; Metathesis; Tamiflu

Rapid bioinspired N-acyliminium ion strategy for the ABC core of the stemona alkaloids - Chavan, Subhash P.; Kalbhor, Dinesh B.; Gonnade, Rajesh G. (Asian Journal of Organic Chemistry, 2023)
A concise and highly diastereoselective bioinspired key cationic cyclization strategy for the asymmetric synthesis of the tricyclic core of the (-)-stemoamide, together with 8,9-bis-epi-stemoamide has been described. The key N-acyliminium ion precursors were accessed from L-tartaric acid and L-malic acid respectively. The use of ethyl acetoacetate derived bifunctional allylidenetriphenylphosphorane reagent in the early stage of the synthetic strategy is advantageous for the rapid construction of highly functionalized key pyrrolo[1,2-& alpha;]azepine frameworks.
Keywords: alkaloids; Biomimetic synthesis; Claisen rearrangement; cyclization; Regioselectivity

Electrochemical generation of N-centered radicals and their reactivity toward cyclization and subsequent C―C bond cleavage - Suryawanshi, Sharad M.; Singh, Mayuri; Samanta, Ramesh C. (Helvetica Chimica Acta, 2026)
N-containing heterocycles are widely used in medicinal chemistry, and they can be synthesized efficiently by the intramolecular cyclization of N-centered radicals. Furthermore, N-centered radicals also act as excellent hydrogen atom transfer (HAT) reagents. On the other hand, nitrogen atoms in the nitrogen-containing heterocycles are used as a handle to cleave stable five and six-membered rings. However, the electrochemical generation of N-centered radicals and their application in forming heterocycles have been extensively studied. Study beyond cyclization remains largely unexplored; in this manuscript, we summarize our new findings as follows. Under electrochemical conditions, the N & horbar;H bond is cleaved, forming an N-centered radical that adds to the double bond in a 6-endo-trig cyclization fashion. The newly formed C-centered radical reacts with oxygen and undergoes C & horbar;C bond cleavage to form the corresponding carbonyl compounds. The reactivity is dependent on the substituents present on nitrogen. In the case of aromatic amine-derived amide, the TEMPO trapping cyclization product was isolated. A mechanism has been proposed to explain the formation of the products.
Keywords: C-C bond cleavage; cyclization; N-centered radical; N-heterocycles; oxidative ring opening